AN INTEGRATION OF BUDDHADHAMMA PRINCIPLE FOR ENHACEMENT OF POLITICAL SOCIALIZATION IN DEMOCRATIC REGIME OF THE YOUTH IN SURAT THANI PROVINCE - HOMTAKO, Kanitta; สุวฑฺโฒ อธิษฐ์; ปิยวีโร เอกกวิน (Thai Interdisciplinary and Sustainability Review, 2024)
The purpose of this paper is to study factors affecting the political socialization of youth in Surat Thani Province. and how to integrate Buddhist principles to solve problems The research uses a combination of methods, namely qualitative research. Collect data from textbooks, concepts, and theories related to research. Key informants were 19 figures or people by means of in-depth interviews and focus group discussions of 11 figures or people to analyze and synthesize descriptive content and quantitative research. Data were collected using questionnaires from a sample of 396 youths aged 15-17 years in Surat Thani Province. Data were analyzed using descriptive statistics, including frequency, percentage, mean, and standard deviation. The results of the research found that factors affecting the promotion of political socialization were overall at a high level when considering each aspect. Religious institutions are at a moderate level. Methods for integrating Buddhist principles to solve youth political behavior problems by integrating the principles of Darundhamma with the Threefold Principles in adjusting appropriate behavior to become a good citizen with creative qualities.